Association of cerebral spinal fluid copper imbalance in amyotrophic lateral sclerosis - Chen, Qiao Yi; Wu, Peng; Wen, Ting; Qin, Xing; Zhang, Ronghua; Jia, Rui; Jin, Jiaoting; Hu, Fangfang; Xie, Xiaoge; Dang, Jingxia (Frontiers in Aging Neuroscience, 2022)
A plethora of environmental risk factors has been persistently implicated in the pathogenesis of amyotrophic lateral sclerosis (ALS), including metal/metalloids. This study aimed to examine potential associations between cerebral spinal fluid (CSF) metal/metalloids and ALS risks. CSF concentrations of copper (Cu), nickel (Ni), mercury (Hg), arsenic (As), manganese (Mn), and iron (Fe) in ALS (spinal- and bulbar-onset) patients and controls were measured using inductively coupled plasma mass spectrometry (ICP-MS). Results from this study revealed marked differences between control, spinal-onset, and bulbar-onset groups.We report that Cu levels were lower in the ALS and spinal-onset groups compared to the control group. Ni level were higher in the spinal-onset group compared to the control and bulbar-onset groups. In addition, associations between CSF metal/metalloid levels with disease severity, sex, and serum triglycerides were also examined to broach the potential relevance of neurotoxic metal/metalloids in ALS disease heterogeneity.